(untitled) - Abd-Alla, Abd-Elfattah (New Yersey, 1976)
Introduced good knowledge of the digital computer principles, design and construction
Keywords: Electronic digital computers,Máy tính điện tử; Design and construction,Thiết kế và cấu trúc